2010
DOI: 10.1089/ten.tea.2009.0517
|View full text |Cite
|
Sign up to set email alerts
|

Repair of Rat Mandibular Bone Defects by Alveolar Osteoblasts in a Novel Plasma-Derived Albumin Scaffold

Abstract: Repair of bone deficiencies in the craniofacial skeleton remains a difficult clinical problem. The aim of this study was to evaluate a novel albumin scaffold seeded with human alveolar osteoblasts and implanted into experimental mandibular defects. An experimental solid protein scaffold was prepared with human plasmatic albumin crossed with a glutaraldehyde-type agent. Microstructure of scaffold and mechanical properties were examined using scanning electron microscopy and a stress-controlled rheometer. Bilate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 37 publications
1
25
0
2
Order By: Relevance
“…Because bone is always under continuous stress, the mechanical properties of the construct implanted into bone are essential for the repair of bone defects. This scaffold has been proven to provide an appropriate mechanical strength for bone reconstruction in a previous study [14]. A porous structure is also a very important element of scaffolds for bone tissue engineering.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Because bone is always under continuous stress, the mechanical properties of the construct implanted into bone are essential for the repair of bone defects. This scaffold has been proven to provide an appropriate mechanical strength for bone reconstruction in a previous study [14]. A porous structure is also a very important element of scaffolds for bone tissue engineering.…”
Section: Discussionmentioning
confidence: 97%
“…In addition, the easy and inexpensive production of this scaffold makes it more suitable for the repair of bone defects than the previous artificial scaffold materials. Different types of cells have been used for bone tissue engineering, including bone marrow cells, periosteal cells, osteoblasts derived directly from bone, and MSCs derived from various tissues [5,14,15,21]. Ideal cells seeded for bone engineering should be able to proliferate quickly, function like osteoblast, be non-immunologic when implanted in vivo, and be biocompatible with scaffold materials [2,22].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…About 7 % (13 out of 175) of the studies showed little healing after the treatment with cellular scaffolds, with compromised efficacy ascribed to inappropriate choice of cells or scaffolds, poor conditions, or insufficient amount of cells. Notably, in eight studies using osteoblast cell sources, four showed no improvement to the healing, with two showing positive results only when BMP-2-transduced cell lines were used [35][36][37][38][39][40][41][42].…”
Section: Behavior Of Engineered Bone Grafts In Vivomentioning
confidence: 99%